In vitro and molecular modeling insights into α-amylase inhibition by tamarind seed-derived trypsin inhibitor: Implications for hyperglycemic control - Larissa Aida Lemos de Souza; Caio Patrício de Souza Sena; Felipe Carlos de Macêdo Oliveira; Raphael Paschoal Serquiz; Ana Júlia Felipe Camelo Aguiar; Amanda Maria de Souza Nascimento; Ana Karoliny Xavier de Gois Silva; Rose de Paiva Chaves; Anna Beatriz Santana Luz; Thais Souza Passos; Davi Serradella Vieira; Ana Heloneida de Araujo Morais (PLoS ONE, 2025)
Inhibitors of enzymes involved in carbohydrate digestion may be a potential option for glycemic control in Diabetes Mellitus. This study aimed to evaluate the effect of the trypsin inhibitor isolated from tamarind seed (Tamarindus indica L.) (TTI) on α-amylase. After confirmation of the obtaining and characterization of the TTI, the in vitro inhibitory activity of the TTI against α-amylase was analyzed. The interaction of the modeled structures’ theoretical TTI (TTIp 56/287) and five of its derived peptides with α-amylase was also evaluated in silico using Docking and Molecular Dynamics, and their functional properties were examined. The Interaction Potential Energy (IPE) and the main interactions of the peptide-α-amylase complex were described using three-dimensional representations. TTI presented 100% antitryptic activity and a molecular mass of approximately 21 kDa. In vitro, inhibition of α-amylase was higher than 37%. These results were corroborated by computational analyses, which demonstrated strong interaction between the TTIp 56/287 complex and its peptides with the enzyme. The Root Mean Square Deviation (RMSD) and Root Mean Square Fluctuation (RMSF) analyses showed good stability. IPE was −705.08 kJ/mol for DTVHDTDGQVPL and −584.11 kJ/mol for TIAPACAPKPAR. Electrostatic interactions stand out, especially the salt bridge, between the main residues that interacted in the complexes (DTVHDTDGQVPL, TIAPACAPKPAR, and TVSQTPIDIPIGLPVR). Additionally, the bioactive potential predicted two candidates with good stability, a long half-life, and bioactivity in an intestinal simulation environment. This is the first report of tamarind trypsin inhibitor or its peptides inhibiting α-amylase. Thus, the amino acid sequences DTVHDTDGQVPL and TIAPACAPKPAR were revealed as candidates that could be tested for action against α-amylase and possibly for glycemic control.